A Cost-Effective and Robust Cell-Based Bioassay Method for Evaluating the Bioactivity of Trastuzumab-like Antibodies - Pooja Bharali; Subhash Chand; Harish Chander (Biomedicines)
Background/Objectives: Trastuzumab is an effective therapeutic intervention for treating HER2-positive breast cancers. The cost-effectiveness, global demand, and patent expiration of trastuzumab have led to the inflow of its biosimilars in the global market. With the rise of biosimilars in the biopharmaceutical market, it has become crucial to ensure that the biosimilar is at par with the original monoclonal antibody (mAb)in terms of efficacy, safety, and quality. Bioassay is one of the critical quality attributes (CQAs), hence developing a reliable and robust bioassay is essential for the evaluation of their biological activity and the harmonization of the quality of these biologics, supporting their safe and effective use in clinical practice. Methods: The present study aimed to develop a robust cell-based bioassay to assess the bioactivity of trastuzumab and its biosimilars for quality control testing. For this purpose, molecular characterization of different HER2-positive breast cancer cell lines of SKBR3, BT474, MDA-MD-453, MDA-MB-175, MCF-7, and MDA-MB-231 was performed to select a suitable cell line for the cell-based bioassay. Results: The SKBR3 cell line was found to express the HER2 receptors significantly higher in comparison to the other cell lines, and it was thereby selected for further bioassay optimization. The biological activity of trastuzumab was determined using the inhibition of proliferation (IOP) assay on the SKBR3, which was optimized based on the parameters of cell seeding density, drug dilution range, and incubation time, and it was further validated as per the compendial guidelines and found valid for the parameters of specificity, accuracy (% relative bias = 0.0067%), precision (repeatability: % GCV = 1.21%), linearity (R2 = 0.99), and range (50% to 200%). Additionally, the biological activity of different trastuzumab biosimilars was assessed using the validated IOP assay and compared to the HER2 binding assay performed by flow cytometry. The biological activity of different trastuzumab biosimilars was found to be comparable to the WHO primary reference standard of trastuzumab in terms of its relative potency using the IOP assay and binding assay by flow cytometry. Conclusions: Thus, an economic and robust cell-based bioassay method was successfully developed to assess the bioactivity of trastuzumab and its biosimilars.